The role of management ethics on administrative creativity – An applied study on a group of school administrators in the Asir educational region – - Al-Tawil, Mona Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to address the issue of the role of management ethics on administrative creativity, an applied study on a group of school administrators in the Asir educational region - Khamis Mushait Governorate, and the study used the descriptive and analytical approach, and where the questionnaire was used as a main tool for data collection in this study, and the study reached a number of Among the most important results are: the presence of a statistically significant effect of administrative ethics in its dimensions on administrative creativity in the school administrations of the Asir educational region, and that there are no statistically significant differences at the level of significance (α = 0.05) in the responses of the respondents on management ethics and administrative creativity in the school administrations of the Asir region In Khamis Mushayt governorate, the following demographic variables are attributed to (gender - age - years of experience - job title - workplace), and there are statistically significant differences at the level of significance (α = 0.05) in the responses of the respondents on management ethics and administrative creativity in the school administrations of the Asir region of the governorate Khamis Mushait attributed to the variable (scientific qualification), and based on these results, the researcher recommended a set of recommendations, the most important of which are: The need to increase The school administrations have created a research and development unit that undertakes the task of studying ways of creativity at the school level.